Trends in Language Formalization in Architecture - Pereira, Franklim Morais (Joelho, 2014)
Alberti’s first attempt to theorize architecture as a formalized language, condensed in its concept of concinnitas, is used as a pretext for the subject of this paper. The path to formalization is a homo sapiens ‘must’. At first, in the everyday use, from primitive pre-discursive languages to the modern dominant language system – speech or discursive semi-formal languages; and since classical Greece, with logical-deductive languages, scientific languages and our age’s zenith of mental representations of the world – theory. Almost every domain of human activity has been subjected to the effort of applying those new methodologies. Architecture could not remain an isolated case. After analyzing some properties of formalized languages, three domains, interior to the architectural activities, are presented. Structures is an architectural field of early formalization (but two millenniums after the first – geometry). Its development has suffered all the pains of growing up, thus having a great diversity of very interesting stories to learn from – the need and difficulties of making epistemological cuts in the open ocean of phenomena, defining the important concepts and ignoring the others, penetrating the essence of reality in very reduced, abstract and synthetic formulations, that, although absolutely general and abstract, don’t loose any semantic or concrete power. It’s what science and theoretical science do. The history and practice of structural science also rise the ‘theory versus methodology’ issue. The second field is real-time building management (the case of intelligent buildings). This is the domain where the more recent advances in formal languages (such as discrete maths, theory of computation, logics, language theory, higher algebras, decision theory) have been applied more often and profoundly. Several particular developments are mentioned, that could be relevant to other fields of architecture – multi-agent optimization, the great complexity of the problem with thousands of interrelated discrete variables, the community of many (human and machine) languages that have to coexist and communicate, the need for a common semantic ground, through ontologies – base for several grammars development. Finally, some remarks on current paths of formalization in the core business of architectural global design, specially on space syntaxes (one of the three major approachs,along with space grammars and architectural ontologies, in the contemporary research). Those remarks concern the problems of empiric vs theoretic; the expressiveness of denotational semantics (relations with other sciences – social, cultural, ideologies); the sophistication of connotational semantics. The question is what is the state of the art – how extensively can they address the global human problems of the city and the building; how their concepts address intensively, in a core minimal theory, the essence of the interaction of architectural action with its environment.